DEVELOPING PBL SCENARIO FOR ONLINE TUTORIALS - Yoga Pamungkas Susani; Prattama Santoso Utomo; Nancy Margarita Rehatta (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Scenario is one of the three main components of Problem-based Learning (PBL) besides students and tutors. Besides being an essential component in triggering interest in learning, scenarios also affect group dynamics and academic achievement. During the COVID-19 pandemic, most of the learning process was conducted online, including PBL tutorial discussions. Distraction during online PBL learning is a challenge that must be faced so that the discussion process can achieve the learning objectives. This condition requires the commitment of tutors and students and engaging scenarios that will also help students and tutors stay focused on the discussion. This article is a recommendation based on the IAMHPE Webinar #5 on the scenario development process to support the online PBL process. This article may provide a guide in developing PBL scenarios.Recommendation: The development of PBL scenarios in pandemic conditions still needs to consider various aspects of preparing a good and immersive scenario. The steps needed are ensuring the scenario development team, determining learning objectives and tutorial issues, designing innovative scenarios, conducting reviews and improving the quality of scenarios regularly, and preparing informative tutor guides.Conclusion: Scenarios for online PBL tutorials must support the application of the four PBL principles, namely constructive, contextual, self-directed learning, and collaborative learning. Each institution needs to create scenarios that are appropriate to its learning context.